DIFFERENT METHODS AND APPLIED LINGUISTIC APPROACHES BY JAVANESE AND PAPUAN LECTURERS - Bunga Nuur Primayu Utami; Imma Kurniawaty (UICELL, 2021)
English teaching cannot be separated with method and approach that used by the lecturers. The aim of this paper is to know the differences between Javanese and Papuan students’ characteristic, the method and strategy that used by each lecturers. The subject of this paper is lecturers in Java and Papua. The writers interest with Java because the location that near from the goverment, automatically the university that has location in Java get much pay attention from the goverment. It difference with Papua that has location at east Indonesia. In terms of facilities and access to government, it is also felt to be lacking. The writer belive that it is become the factor that influence the teaching learning, especially English teaching that need a lot of facilities. That is become the reason why the writer choose to compare them.The method of this paper is descriptive qualitative. The result of this paper is conclude that Papuan students have to give more attention first before starting the lesson than Javanese students. It is approriate the lecturer of Papua used Total Phisychal Response method and Humanism aprroach, furthermore in Java the lecturer used Natural Approch and Behaviorism approach to reinforce the students idea or knowledge. Keywords : Total Physical Response, Natural Approach, Behaviorism, Humanism